Delayed neurological deficits after endovascular placement of a pipeline embolisation device: clinical manifestation and treatment. (23rd March 2018) - Sablani, Naveen; Hasan, Maryam Mumtaz; Shrestha, Ashik; Farkas, Jeffrey
Abstract : Endovascular treatment has been the mainstay of therapy for repair of both ruptured and unruptured cerebral aneurysms. Flow diverter devices offer a new option for the treatment of complex aneurysms that were previously not amenable to coiling. Procedural adverse effects include intracranial haemorrhage and ischaemic stroke, which usually occur on the same day. Delayed complications are rare. We report a case of a patient who underwent placement of a pipeline embolisation device and developed delayed neurological deficits, which were thought to be an inflammatory reaction to the hydrophilic coating used in guidewires and microcatheters. Our patient was treated with a course of steroids, with improvement of her neurological deficits and resolution of MRI findings. As the use of flow diverter devices has increased, variable and delayed complications of such therapy are increasingly being reported in the literature.